HUBUNGAN PERILAKU PERAWATAN KAKI DENGAN KUALITAS HIDUP PASIEN DIABETES MELITUS DI RSU MUHAMMADIYAH DAN KLINIK RULIA MEDIKA PONOROGO - Nelly Adelian Nur Safitri; Lina Ema Purwanti; Sri Andayani (Health Sciences Journal, 2022)
Foot care behavior is a part of primary prevention efforts in diabetic foot management. Foot care aims to prevent the occurence of chronic complications in the form of diabetic neuropathy or the death of nerves of the feet so that it can cause diabetic foot ulcers. This research aims to analyze the relationship between foot care behavior and the quality of life of Diabetes Mellitus patients at RSU Muhammadiyah and Klinik Rulia Medika Ponorogo. The research design used is a correlation study. The population in this study were Diabetes Mellitus patients at RSU Muhammadiyah and Klinik Rulia Medika Ponorogo, totalling 41 patients. The sampling technique was purposive sampling with a sample size of 41 patients. The data were collected with foot care behavior questionnaire and quality of life questionaire (WHOQoL-BREF). Data were analyzed using Chi-Square test using application SPSS. The results showed that the majority of patients had positive foot care behavior as many as 27 patients (65,9%), and 22 patients (53,7%) high quality of life and 19 patients (46,3%) medium quality of life. From this research, it was found that a significant value was 0,020 (α 0,05) so that there was a relationship between foot care behavior and the quality of life in Diabetes Melitus patients at RSU Muhammadiyah and Klinik Rulia Medika Ponorogo. Positive behavior is needed in foot care so that the risk of complications can be minimized, especially the risk of diabetic foot ulcers which will also have an impact on the quality of life in patients with Diabetes Mellitus.